2006
DOI: 10.1149/1.2184070
|View full text |Cite
|
Sign up to set email alerts
|

Bias-Temperature Stability of Ti–Si–N–O Films

Abstract: Copper shows a tendency to drift into contiguous dielectric material under bias and temperature stressing. The stability of different compositions ͑by changing silane gas flow rate͒ of Ti-Si-N-O films has been investigated using metal-oxide-semiconductor ͑MOS͒ capacitors. MOS samples preannealed at 250°C and subjected to bias temperature stressing ͑BTS͒ at 150°C, 200°C under an electrical field of 0.5 or 1 MV/cm show stable capacitance-voltage behavior with no flatband voltage shift from as-annealed to 90 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
4
0
3
Order By: Relevance
“…Las muestras presentan fases cristalinas con una orientación preferencial (220), excepto la muestra M2 que presenta una orientación preferencial (200). La orientación cristalina (220), es más eficiente que la (111) y (200), ideal para poder utilizarse en recubrimientos como barreras para los circuitos integrados (Ee et al, 2006a(Ee et al, , 2006b, garantizando así el éxito de los dispositivos electrónicos. No obstante, esta orientación cristalina preferencial no es tan fácil de obtener, ya que la estructura columnar del TiN, presenta la orientación cristalina preferencial (111) ó (200).…”
Section: Resultados Y Discusionesunclassified
See 2 more Smart Citations
“…Las muestras presentan fases cristalinas con una orientación preferencial (220), excepto la muestra M2 que presenta una orientación preferencial (200). La orientación cristalina (220), es más eficiente que la (111) y (200), ideal para poder utilizarse en recubrimientos como barreras para los circuitos integrados (Ee et al, 2006a(Ee et al, , 2006b, garantizando así el éxito de los dispositivos electrónicos. No obstante, esta orientación cristalina preferencial no es tan fácil de obtener, ya que la estructura columnar del TiN, presenta la orientación cristalina preferencial (111) ó (200).…”
Section: Resultados Y Discusionesunclassified
“…Recientemente se han fabricado películas de TiSiNO para que actúen como barreras contra la difusión (Ee et al, 2006b(Ee et al, , 2006c(Ee et al, , 2006dShalaeva et al, 1999), debido a sus prometedoras propiedades, que los hacen fuertes candidatos para la siguiente generación de barreras de difusión en la tecnología CMOS. Estudios realizados sobre este sistema cuaternario, revelan que estos recubrimientos están formados de nanocristales embebidos generalmente en fases amorfas de Ti-O, Si-O, Si-N y Si-N-O (Shalaeva et al, 1999).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Detailed analysis carried out elsewhere [10] has indicated that this small flatband voltage shift is due to the interface states and/or hot holes injection from the Si substrate into the oxide layer. The reason for such a shift with high Si content could be explained by the interface defects generated during deposition process.…”
Section: Barrier Performance Of Ti-si -N -O Filmsmentioning
confidence: 99%
“…(1) Thermodynamical stablility when in contact with materials: A viable barrier material must not react with copper or underlying substrate under the thermal, mechanical and electrical stress conditions encountered in subsequent processing steps or normal operating conditions (2) High density so as to eliminate diffusion across voids, defects or loosely packed grain boundaries (3) Microstructure which minimizes grain boundaries as diffusion paths (4) Low contact resistance and a reasonable thermal conductivity (5) Excellent adhesion to all materials used in the metallization scheme (6) Electrochemical potential close to that of surrounding materials in order to avoid the formation of galvanic corrosion cells with the metallization layers (7) Low film stresses [Baluffi, 1975] and enhanced resistance to thermal and mechanical stresses (8) thickness requirements for copper are anticipated to be less than 5.6 nm [ITRS 2005] as shown in Table 1-1.…”
Section: Introductionmentioning
confidence: 99%